Measuring prospective Korean technology teachers’ attitudes towards technology subjects in secondary schools - Young-heung Kim; Dooyong Cho (Jurnal Pendidikan Vokasi, 2024)
This study aimed to develop and validate a measurement tool for assessing prospective technology teachers’ attitudes toward technology subjects in Korea and to examine differences across student groups. A major teacher education university in Korea was selected, and a survey was conducted among 80 undergraduate students from the first to fourth year who were preparing to become technology teachers. The instrument development process involved four stages: item generation, preliminary construction, validity testing, and reliability testing. Data were collected through postal and online questionnaires and analyzed using exploratory factor analysis and reliability tests. Attitudes toward technology subjects were defined as consistent psychological tendencies expressed in beliefs, affective feelings, and behavioral intentions. Results showed that the developed tool demonstrated strong validity and reliability, with three clear dimensions. Overall, students reported a relatively high attitude score (M = 4.15), with beliefs about technology education receiving the highest average score (M = 4.59). Significant differences were found based on gender, with female students showing stronger beliefs about technology subjects, and by grade level, where fourth-year students exhibited higher behavioral intentions compared to first-year students. These findings indicate that while prospective technology teachers in Korea hold strong beliefs and intentions toward technology subjects, their affective feelings remain less positive. This study contributes to vocational and teacher education research by providing a validated instrument for measuring technology education attitudes and by offering insights for curriculum design that fosters positive attitudes in future technology educators.